The spanish’ political agenda against early school leaving: LOMCE against international evidences - Tarabini, Aina; Montes, Alejandro (Avances en Supervisión Educativa, 2015)
Combating Early School Leaving (ESL) is a central item of the Spanish educational political agenda. In fact, one of the main objectives of the current Educational Law (Organic Law for the Improvement of the Quality of Education-LOMCE) is to reduce the high levels of ESL and to improve the global results of the Spanish educational system. The aim of the article is to prove, based on international scientific evidence, that the new Law’s proposals addressed to reduce ESL represent a key risk in terms of educational equity and also in terms of educational efficiency and quality. The analysis is based on a systematic evaluation of three aspects of the Law: the early tracking; the focus on academic achievement; and the omission of preventive strategies to tackle ESL.
Keywords: early school leaving; educational equity; educational success; education policies; tracking; LOMCE